Valenz(h)uel(l)as : marcas de resistência, memória e cicatriz da ditadura militar argentina na narrativa de Luisa Valenzuela - Vogas, Vitor Bourguignon (2016)
From 1976 to 1983, Argentina was governed by a military dictatorship. In order to keep population under control and eradicate any threaten to the established order, the authoritarian government has performed some strategies of domination in the context of the so-called guerra sucia. In this master’s dissertation, we aim to prove with large evidence that Luisa Valenzuela – particularly between the 70’s and the 90’s – has practiced what she would consider to be the ethical commitment of a writer: denouncing issues that others wouldn’t even dare mentioning. Inspired by the concept of resistance in literature as defined by Bosi, we intend to demonstrate how Valenzuela has developed a narrative of resistance (without sacrificing neither the aesthetic richness of her writings nor the manipulation of language), both as the plot of her stories and (mostly) as the way she approached her arguments. For achieving that, she has used what we will call “strategies of resistance”: to stand up against the monopoly of speech, she’s chosen the plurality of voices, the relativization of reality and the exposure of the manipulation of the literary enouncement (thus of any other speech); as oppose to the elimination of any difference, she’s preferred ambiguity and emphasized the same individualities the system would rather delete; to resist the spread of fear and the methodical use of violence as a government policy, she’s broadly adopted humor and sex, besides approaching violence itself in an erotic way; to fight massive silence and oblivion, she had the courage of leaving a testimony of the unnamable horror, yet through proudly fictional books. Conscious of the destabilizing power of writing, Valenzuela used the literary language as a weapon (as she would call it), as lethal and manageable as the poison of the toads spited out of one of her character’s mouth every time she spoke.